Analysis Of Orthoptera in The Territory of Central Uzbekistan (Texas Journal of Agriculture and Biological Sciences, 2023)
According to the geographical range of orthopteran insects of Central Uzbekistan, it belongs to 9 groups: Trans-Palaearctic species 24, European-Siberian species 7, European-Kazakh species 10, EuropeanCentral Asian species 6, Kazakhstan - Western Mongolian species 5, Kazakh-Mongolian species 5, Central Asian-Kazakh species 10, Central Asian species 32, Central Asian species. There are 12 species in Asia and Kazakhstan.